Tooth fairy 2 - Zamm, Alex.; Larry, the Cable Guy.; Reiter, Brady; Beute, Erin.; Mackey, David; Zazove, Ben.; Piddock, Jim, 1956-; Twentieth Century Fox Home Entertainment, Inc.; Walden Media (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2012)
Larry Guthrie is a fun-loving guy with a serious mission: to win back Brooke, the love of his life. But when Larry upsets a small boy with a loose tooth where Brooke works, he's 'sentenced' to become a real Tooth Fairy. It's tutu times the laughs watching Larry strut his stuff in pink tights and ballet shoes as he tries to restore the boy's faith before Brooke marries the wrong man, and he only has ten days to git-r-done!
Based on characters created by Jim Piddock.
Release date: Mar. 6, 2012.
Special features: Why do I lose my baby teeth? ; Return to Fairyland--making Tooth fairy 2.
Music, Chris Hajian ; editor, Heath Ryan ; production designer, Charlie Daboub ; director of photography, Levie Isaacks.
Larry The Cable Guy, Brady Reiter, Erin Beute, David Mackey.
MPAA rating: PG; for some mild rude humor.
Keywords: Tooth Fairy (Legendary character) -- Drama; Man-woman relationships -- Drama; Film sequels; Comedy films; Video recordings for the hearing impaired